Studi karakteristik Sedimen di Estuari Delta Mahakam Kalimantan Timur - Anggara, Geogy; Mandang, Idris; Munir, Rahmiati (GEOSAINS KUTAI BASIN, 2021)
The Mahakam Delta has complex characteristics. It has river branches to connect directly in the Makassar Strait. River discharge carries sediments from upstream to the high-salinity water in Estuary which causes mixing. The purposes of this study are to determine the characteristics of sediments and to know the pattern of sediment distribution in the Estuary of Mahakam Delta. The value of the manual processing of sediments become the initial value in modeling the pattern of sediment distribution using ECOMSED model. The model is run for 40 days (07 July - 16 August 2019). Discharge and tidal also use in the running data. The results of manual processing show the characteristics of muddy sediments with an average of 0.002 mm. The simulation results show that the pattern of sediment distribution carried by surface currents. The highest of sediment concentration when the high tide is on the Estuary and on offshore when the low tide. Keywords: The Mahakam Delta, Sediment, Distribution pattern, Sediment Characteristics